If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 1 = 6x + -13 Reorder the terms: 1 + 3y = 6x + -13 Reorder the terms: 1 + 3y = -13 + 6x Solving 1 + 3y = -13 + 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3y = -13 + -1 + 6x Combine like terms: 1 + -1 = 0 0 + 3y = -13 + -1 + 6x 3y = -13 + -1 + 6x Combine like terms: -13 + -1 = -14 3y = -14 + 6x Divide each side by '3'. y = -4.666666667 + 2x Simplifying y = -4.666666667 + 2x
| 4(k+5)=.16(18k+18) | | 1/4a-9=1/2a | | f(x)=x^2+5x-36 | | [-10-(64)/256= | | 12n-1n+3n= | | 10x-13y=-31 | | 1/2a-9=1/4a | | 10x-13y=-32 | | 2(3+7x)=118 | | 10+7*4=38 | | 3n+7n-4= | | 5y-25=99+y | | -8+4u=-32 | | 432/2/4325/34435 | | 4x+51=6x+9 | | 2n+7-n+2= | | x+7x-5= | | 56=6h | | 6y-25=95+y | | 24=c-8 | | 4x+7=23+2x | | 40+3x+20+x=180 | | https://homebase.schoolnet.com/files/assess_files/cf1ae17e-8d5e-4dca-981c-c9ee7af1d787/_s_I373865_1.png | | 6-7a-14=8+a | | 4x+81=13x+36 | | 9+2j=17 | | 7x+5-3y=-31 | | 12x-19y+27=1 | | 6(x-5)-3w=12 | | 3x+3*5=27 | | 10=4+3s | | 4x^3-15x^2-25x= |